Payment size, negative equity, and mortgage default - Andreas Fuster; Paul S. Willen (Federal Reserve Bank of Boston, 2012)
Surprisingly little is known about the importance of mortgage payment size for default, as efforts to measure the treatment effect of rate increases or loan modifications are confounded by borrower selection. We study a sample of hybrid adjustable-rate mortgages that have experienced large rate reductions over the past years and are largely immune to these selection concerns. We show that interest rate changes dramatically affect repayment behavior. Our estimates imply that cutting a borrower's payment in half reduces his hazard of becoming delinquent by about two-thirds, an effect that is approximately equivalent to lowering the borrower's combined loan-to-value ratio from 145 to 95 (holding the payment fixed). These findings shed light on the driving forces behind default behavior and have important implications for public policy.
Keywords: G21; E43; 330; Hypothek; Kredittilgung; Kreditrisiko; Konsumentenverhalten; Schätzung; USA